BRCA1 foci test as a predictive biomarker of olaparib response in ovarian cancer patient-derived xenograft models - Guffanti, Federica; Mengoli, Ilaria; Alvisi, Maria Francesca; Dellavedova, Giulia; Giavazzi, Raffaella; Fruscio, Robert; Rulli, Eliana; Damia, Giovanna (Frontiers in Pharmacology, 2024)
Standard therapy for high grade ovarian carcinoma includes surgery followed by platinum-based chemotherapy and poly-ADP ribose polymerase inhibitors (PARPi). Deficiency in homologous recombination repair (HRD) characterizes almost half of high grade ovarian carcinomas and is due to genetic and epigenetic alterations in genes involved in HR repair, mainly BRCA1/BRCA2, and predicts response to PARPi. The academic and commercial tests set up to define the HRD status of the tumor rely on DNA sequencing analysis, while functional tests as the RAD51 foci assay, are currently under study, but none has been already validated and is available for patients. In a well characterized ovarian carcinoma patient-derived xenograft platform whose response to cisplatin and olaparib, a PARPi, is known, we assessed the association between BRCA1 foci score, determined in formalin-fixed paraffin embedded tumor slices with an immunofluorescence technique, with other HRD biomarkers and we explored the potential of BRCA1 foci test to predict tumors’ response to cisplatin and olaparib. The BRCA1 foci score associated with both tumors’ HRD status and RAD51 foci score. Low BRCA1 foci score predicted response to olaparib and cisplatin, while a high score associated with resistance to therapy. As we have recently published that low RAD51 foci score predicted olaparib sensitivity in our xenobank, we combined the two scores and showed that the predictive value was better than with the single tests. This study reports for the first time the capacity of the BRCA1 foci test to identify HRD ovarian carcinomas and to possibly predict response to olaparib.